Sistem Budaya Kaum Urban - S Sumarjoko; Farinka Nurrahmah Azizah (Jurnal Ilmiah Citra Ilmu : Kajian Kebudayaan dan Keislaman, 2020)
This article discusses a person's factor in choosing to be an urban actor, a phenomenon that underlies some millennials to choose being an urban. Research method used is field research with a qualitative-descriptive analysis method for millennials in Boto Village, Kembang, Nanggunan District as urban actors. Based on the results of this study, it shows that being an urban actor is not due to population explosion problem or high poverty rates. However, the occurrence of urbanization because it has become a trend, also concept of hijrah emergence, and because of despair over something problem. Urban actors also generate new ideologies, new cultures, new and individualistic, private, consumptive, extravagant and narcissistic views of life.